Return on Investment: A Placebo for the Chief Financial Officer... And Other Paradoxes - Peter Andru; Alexei Botchkarev (The Evaluation Center at Western Michigan University, 2011)
Background: Return on investment (ROI) is one of the most popular evaluation metrics. ROI analysis (when applied correctly) is a powerful tool of evaluating existing information systems and making informed decisions on the acquisitions. However, practical use of the ROI is complicated by a number of uncertainties and controversies. The article reveals some of these controversies in an engaging and thought-provocative manner. Purpose: The intent of this note is to highlight several of the ROI paradoxes in a format of an opinion or a viewpoint with a hope that drawing attention of the ROI practitioners and researchers to these issues will contribute to more transparent and responsible application of the ROI evaluation. Setting:  Not applicable. Intervention: Not applicable. Research Design: Not applicable. Data Collection and Analysis: Review of current practice. Findings:  The article reveals three weaknesses of the ROI evaluations, which in the absence of the commonly accepted ROI standard, can make results of the ROI evaluations uncertain or questionable.  Keywords:  return on investment; ROI; paradox; evaluation